A Pilot Prospective Randomized Control Trial Comparing Exercises Using Videogame Therapy to Standard Physical Therapy: 6 Months Follow-Up. Issue 5 (September 2015) - Parry, Ingrid; Painting, Lynda; Bagley, Anita; Kawada, Jason; Molitor, Fred; Sen, Soman; Greenhalgh, David G.; Palmieri, Tina L.
Abstract : Commercially available, interactive videogames that use body movements for interaction are used clinically in burn rehabilitation and have been shown to facilitate functional range of motion (ROM) but their efficacy with burn patients has not yet been proven. The purpose of this pilot randomized control study was to prospectively compare planar and functional ROM, compliance, pain, enjoyment, and exertion in pediatric burn patients receiving two types of rehabilitation therapy. Seventeen school-aged children with 31 affected limbs who demonstrated limited shoulder ROM from burn injury were randomized to receive exercises using either standard therapy ROM activities (ST) or interactive videogame therapy (VGT). Patients received 3 weeks of the designated therapy intervention twice daily. They were then given a corresponding home program of the same type of therapy to perform regularly for 6 months. Standard goniometry and three-dimensional motion analysis during functional tasks were used to assess ROM. Measures were taken at baseline, 3 weeks, 3 months, and 6 months. Pain was measured before and after each treatment session during the 3-week intervention. There was no difference in compliance, enjoyment, or exertion between the groups. Patients in both the ST and VGT groups showed significant improvement in shoulder flexion ( P < .001), shoulder abduction ( P <.001), shoulder external rotation ( P = .01), and elbow flexion ( P = .004) ROM from baseline to 6 months as measured with goniometry. Subjects also showed significant gains in elbow flexion ( P = .04) during hand to head and shoulder flexion ( P = .04) during high reach. There was no difference in ROM gains between the groups. Within group comparison showed that the VGT group had significantly more recovery of ROM during the first 3 weeks than any other timeframe in the study, whereas ST had most gains at 3 months. There was a significant difference between the groups in the subjects' pain response. ST subjects showed an increase in pain during the intervention, whereas VGT subjects did not (VGT: r = .047, ST: r = .18; P = .015). In this study, interactive videogames were equally effective as traditional therapy for overall ROM gains and resulted in quicker recovery of motion with less pain experienced. Such videogames are a useful adjunct to therapy and should be considered as part of a holistic approach to rehabilitation within the hospital and at home after discharge in pediatric patients recovering from burn injury.